ANALISIS IMPLEMENTASI KARTU KREDIT PEMERINTAH DAERAH (KKPD) PADA PEMENRINTAH PROVINSI SULAWESI SELATAN - Siagian, Boyke Martz (Gapenas Publisher, 2025)
This study analyzes the implementation of Local Government Credit Cards (KKPD) in the South Sulawesi Provincial Government. The implementation of the KKPD aims to increase efficiency and transparency in regional financial management. This study identifies the implementation process, obstacles faced, and the impact of KKPD on regional financial management. The results of the study show that although the implementation of the KKPD has started well, there are still obstacles related to networking and socialization in several regions. The positive impact of the KKPD includes reducing the use of cash and increasing the transparency of financial transactions. This study provides recommendations for improving the KKPD implementation process in the future.